A BIOCHEMICAL STUDY TO EVALUATE THE EFFICIENCY OF SOME LOCAL CULTURE MEDIA IN THE GROWTH OF THE REISHI MUSHROOM - A. Th. Mahmoud; I. A. Abed; O. H. M. Almohammedi (مجلة الأنبار للعلوم الزراعية)
Despite the significant nutritional and medicinal value of Reishi mushrooms few studies have examined the effectiveness of local media in enhancing their productivity. This study evaluated the efficiency of various media derived from the abundant raw materials in the Iraqi environment. Organic compounds from the biomass of materials such as sugarcane bagasse, sycamore tree waste, and wood shavings were used to grow local and Chinese strains of the Reishi mushroom in the laboratory and their levels of amino acids, phenols, flavonoids, and vitamin D3 measured. The results show sugarcane bagasse as the most efficient in promoting the growth of both isolates for all parameters compared to the other media. The local strain was superior in growth terms for all media compared to the Chinese strain. The study concluded that levels of organic compounds in biomass varied significantly depending on the type of medium and the cultivated strain. Alanine had the highest concentration among all amino acids while arginine was the lowest, and phenols and flavonoids had higher concentrations in the Iraqi strain grown on sugarcane bagasse compared to the Chinese strain for all mediums. The results for vitamin D3 were also consistent with the other organic compounds in terms of the superiority of the sugarcane bagasse medium in stimulating production in the Iraqi compared to the Chinese isolate, and for all media.